2010
DOI: 10.1371/journal.pbio.1000545
|View full text |Cite
|
Sign up to set email alerts
|

The Translation Initiation Factor 3f (eIF3f) Exhibits a Deubiquitinase Activity Regulating Notch Activation

Abstract: The translation initiation factor complex eIF3f has an intrinsic deubiquitinase activity and regulates the Notch signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 57 publications
7
85
0
Order By: Relevance
“…Notch receptor endocytosis requires mono-ubiquitylation of the receptor at lysine 1749 (Gupta-Rossi et al, 2004), and, recently, this mono-ubiquitylation event has been shown to be followed by deubiquitylation mediated by elF3f, previously thought to solely constitute a subunit of translation initiation factor E74-like factor 3 (Elf3), which is required for Notch to be processed by -secretase (Moretti et al, 2010). The putative E3 ubiquitin ligase Deltex, which has been implicated in the regulation of Notch processing and internalization in several studies (Diederich et al, 1994;Hori et al, 2004;Matsuno et al, 1995;Wilkin et al, 2008;Yamada et al, 2011), serves as a bridging protein between elF3f and Notch in early endosomes (Moretti et al, 2010). Deltex has been described as both a positive (Fuwa et al, 2006;Matsuno et al, 1995;Matsuno et al, 2002;Wilkin et al, 2008) and a negative (Sestan et al, 1999;Mukherjee et al, 2005) regulator of Notch signaling, and Deltex appears to be required for Notch signaling in some, but not all, developmental processes in Drosophila (Fuwa et al, 2006).…”
Section: Endocytosis and Trafficking Of Processed Notch Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch receptor endocytosis requires mono-ubiquitylation of the receptor at lysine 1749 (Gupta-Rossi et al, 2004), and, recently, this mono-ubiquitylation event has been shown to be followed by deubiquitylation mediated by elF3f, previously thought to solely constitute a subunit of translation initiation factor E74-like factor 3 (Elf3), which is required for Notch to be processed by -secretase (Moretti et al, 2010). The putative E3 ubiquitin ligase Deltex, which has been implicated in the regulation of Notch processing and internalization in several studies (Diederich et al, 1994;Hori et al, 2004;Matsuno et al, 1995;Wilkin et al, 2008;Yamada et al, 2011), serves as a bridging protein between elF3f and Notch in early endosomes (Moretti et al, 2010). Deltex has been described as both a positive (Fuwa et al, 2006;Matsuno et al, 1995;Matsuno et al, 2002;Wilkin et al, 2008) and a negative (Sestan et al, 1999;Mukherjee et al, 2005) regulator of Notch signaling, and Deltex appears to be required for Notch signaling in some, but not all, developmental processes in Drosophila (Fuwa et al, 2006).…”
Section: Endocytosis and Trafficking Of Processed Notch Receptorsmentioning
confidence: 99%
“…It is thus possible that the localization of Notch cleavage is variable and constitutes another level of signal fine-tuning that is dependent on cell context (Tagami et al, 2008). Notch receptor endocytosis requires mono-ubiquitylation of the receptor at lysine 1749 (Gupta-Rossi et al, 2004), and, recently, this mono-ubiquitylation event has been shown to be followed by deubiquitylation mediated by elF3f, previously thought to solely constitute a subunit of translation initiation factor E74-like factor 3 (Elf3), which is required for Notch to be processed by -secretase (Moretti et al, 2010). The putative E3 ubiquitin ligase Deltex, which has been implicated in the regulation of Notch processing and internalization in several studies (Diederich et al, 1994;Hori et al, 2004;Matsuno et al, 1995;Wilkin et al, 2008;Yamada et al, 2011), serves as a bridging protein between elF3f and Notch in early endosomes (Moretti et al, 2010).…”
Section: Endocytosis and Trafficking Of Processed Notch Receptorsmentioning
confidence: 99%
“…These cells are devoid of any active Notch ligand and stably express low levels of full-length human Notch, Notch-FL, which remains transcriptionally inactive unless it is activated by its ligands. In this case, it is tagged in the extracellular domain with an HA epitope (9).…”
Section: Identification Of Usp12 As a Candidate Dub Acting Onmentioning
confidence: 99%
“…Proper routing of the internalized Notch receptor may also be important for preventing ligand-independent activation, and Notch signaling defects are indeed linked to impaired endocytic trafficking and endosome acidification [4,16]. The internalization step appears to be controlled by monoubiquitylation of the Notch receptor at the cell surface [4], followed by a deubiquitylation event, which is required for signaling activation [17]. Deltex, an E3 ubiquitin ligase, is a regulator of Notch internalization and processing, although whether it functions to enhance or reduce Notch signaling appears to be cell context-dependent [18][19][20].…”
Section: Introductionmentioning
confidence: 99%